Neck and shoulder pain in nurses working in seven wards of Tygerberg hospital : quantifying the problem and exploring the risks - Altmann, Janet Rosemary (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2011.